2010
DOI: 10.3748/wjg.v16.i29.3704
|View full text |Cite
|
Sign up to set email alerts
|

Is autoimmune hepatitis a frequent finding among HCV patients with intense interface hepatitis?

Abstract: Although possible, overlap with autoimmune hepatitis is a very rare association in HCV-infected patients with intense interface hepatitis, an unusual presentation which seems to be related to other host variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
0
13
0
3
Order By: Relevance
“…Whether intense interface hepatitis in HCV infected patients is caused by concurrent AIH was retrospectively studied [90]. In 92 patients with HCV infection, only 2% of biopsies had intense interface hepatitis and other histological findings typical of AIH.…”
Section: Concomitant Autoimmune Hepatitis and Other Chronic Liver Dismentioning
confidence: 99%
“…Whether intense interface hepatitis in HCV infected patients is caused by concurrent AIH was retrospectively studied [90]. In 92 patients with HCV infection, only 2% of biopsies had intense interface hepatitis and other histological findings typical of AIH.…”
Section: Concomitant Autoimmune Hepatitis and Other Chronic Liver Dismentioning
confidence: 99%
“…However, other positions of the simplified IAIHG scoring system were not fulfilled: the median gammaglobulin level was not different from the other hepatitis C patients, and only a very small fraction of the 92 patients with interface hepatitis carried SMA or LKM antibodies. Although approximately 12% of all patients generated ANA there was no correlation with interface hepatitis, and application of the simplified IAIHG scoring system revealed only one single case of definite AIH . Thus, rather than proving that HCV infection might lead to AIH, the study demonstrates that interface hepatitis is a histological pattern that is present in some patients with hepatitis C.…”
Section: Hepatitis Virusesmentioning
confidence: 72%
“…SMA and ANA, which are characteristic for AIH-1, have been found in up to 66% and 41% of HCV patients, respectively [43]. Recently, a large study was conducted in Brazil with the goal to assess the frequency of AIH in patients with chronic HCV-infection [44]. The authors analyzed liver biopsies from 1759 chronic hepatitis C patients and found intense interface hepatitis compatible with AIH in biopsies of 92 patients.…”
Section: Hepatitis Virusesmentioning
confidence: 98%
“…In contrast, ANA were found more frequently (∼12% of HCV-infected patients), but there was no correlation with the presence of intense interface hepatitis. Finally, following the scoring system of the IAIHG [22] only one patient was classified for definite AIH [44]. This study indicates that interface hepatitis might, although uncommon, also constitute a histological pattern in some patients with hepatitis C.…”
Section: Hepatitis Virusesmentioning
confidence: 99%